Application of a kiln drying technique to Quercus suber L. cork planks - Carpintero, E.; Jurado, M.; Prades, C. (Food and Bioproducts Processing, 2014)
At present, all of the cork used to manufacture natural stoppers is air dried for a minimum of 6 months. This study evaluates the feasibility of applying a kiln drying technique to cork planks. We used a sample of 65 planks, each of which was divided into two pieces. One sub-set of planks was air dried for 6 months following the traditional procedure, while the other was kiln dried for 14 days. The evolution of moisture content was controlled, and both methods were compared by means of a statistical analysis of the thickness, quality, porosity coefficient, color and compressive properties of the cork. The reduction in moisture content was similar for both traditional air drying and kiln drying. At the end of the drying, cork thickness increased with both methods, although a larger increase was observed for the kiln drying method. Statistically significant differences were not found for the mean porosity coefficient or quality. Although statistically significant differences in the color of the cork were detected, it would be necessary to verify if such differences are detectable by the human eye. No differences were found in the compressive properties of the cork for a significance level of less than 1%. This feasibility study concludes that kiln drying is a suitable technique as it significantly reduces the drying time and holding costs of the raw material. The application of this technique would constitute an innovation in the transformation process by controlling the climatic variables that affect the drying process.
Keywords: Compressive properties; Kiln drying; Moisture content; Quality; Thickness; Traditional air drying